Does topical amethocaine gel reduce the pain of venepuncture in newborn infants? A randomised double blind controlled trial. Issue 3 (1st November 2000) - Jain, A; Rutter, N
Abstract : BACKGROUND: Topical amethocaine provides effective pain relief during venepuncture in children, and has been shown to have a local anaesthetic action in the newborn. AIM: To investigate the effect of topical amethocaine on the pain of venepuncture in the newborn. DESIGN: Randomised double blind placebo controlled trial. SUBJECTS: Forty newborn infants, gestation 27–41 weeks (median 33), age 2–17 days (median 7), undergoing routine venepuncture. METHOD: A 1.5 g portion of 4% (w/w) amethocaine gel (Ametop; Smith and Nephew, Hull, UK) or placebo was applied to the skin under occlusion for one hour, then wiped away. Venepuncture was performed five minutes later. Facial reaction and cry were recorded on videotape. Pain was assessed using a validated adaptation of the neonatal facial coding system. Five features were scored at one second intervals for five seconds before and after venepuncture. No or minimal pain was defined as a cumulative score of below 10 (out of 25) in the five seconds after needle insertion. Each author scored the tapes independently. RESULTS: There was close agreement on scoring of the tapes. One infant was excluded because of restlessness before the venepuncture. Of 19 amethocaine treated infants, 16 (84%) showed little or no pain compared with six of 20 (30%) in the placebo group (p = 0.001). The median cumulative neonatal facial coding system score over five seconds after needle insertion was 3 compared with 16 in the placebo group (p = 0.001). Of the 19 amethocaine treated infants, 15 (79%) did not cry compared with five of 20 (25%) placebo treated infants (p = 0.001). No local reaction to amethocaine was seen. CONCLUSION: Topical amethocaine provides effective pain relief during venepuncture in the newborn.